Identification of predictive factors of response to the BH3‐mimetic molecule ABT‐737: An ex vivo experiment in human serous ovarian carcinoma. Issue 5 (8th August 2014) - Lheureux, Stéphanie; N'Diaye, Monique; Blanc‐Fournier, Cécile; Dugué, Audrey Emmanuelle; Clarisse, Bénédicte; Dutoit, Soizic; Giffard, Florence; Abeilard, Edwige; Briand, Mélanie; Labiche, Alexandre; Grellard, Jean‐Michel; Crouet, Hubert; et al.
<x xml:space="preserve">Abstract</x> Ovarian cancers are addicted to Bcl‐xL and Mcl‐1, antiapoptotic members of the Bcl‐2 family. Bcl‐xL can be inhibited by the BH3‐mimetic ABT‐737. In vitro, ABT‐737 can induce apoptosis of cancer cells, and its activity is potentiated by Mcl‐1 inactivation. Herein, we assessed the sensitivity of human ovarian tumor nodes to ABT‐737 when combined with carboplatin, which can indirectly inhibit Mcl‐1. Fresh samples from 25 patients with high‐grade serous ovarian cancer (HGSOC) who were chemo‐naïve and had undergone surgery were prospectively exposed ex vivo to ABT‐737 ± carboplatin. The treatment effect was studied on sliced tumor nodes by assessment of cleaved‐caspase 3 immunostaining. We also studied the association between baseline Bcl‐2 family protein expression (via immunohistochemistry) and the response of nodes to treatment. ABT‐737 induced apoptosis as a single agent but its efficacy was not improved by the addition of carboplatin. Bim was frequently expressed (20/25) and its absence or low expression was associated with the absence of response to ABT‐737, p value = 0.019 by Fisher's test and sensitivity = 93%, (95% confidence interval, 66–100). Moreover, we observed that in tumors in which Bim was expressed, a low expression of phospho‐Erk1/2 or Mcl‐1 improved the proportion of responses. This pilot study showed that ABT‐737 has promise as monotherapy for HGSOC in a specific subgroup of tumors. Bim, Mcl‐1, and phospho‐Erk1/2 appeared to be relevant biomarkers that could be used for the selection of patients in the design of clinical trials using Navitoclax (an orally available compound related to ABT‐737).